Athlete level, sport-type, and gender influences on training, mental health, and sleep during the early COVID-19 lockdown in Malaysia - Washif, Jad Adrian; Kok, Lian-Yee; James, Carl; Beaven, Christopher Martyn; Farooq, Abdulaziz; Pyne, David B.; Chamari, Karim (Frontiers in Physiology, 2023)
Purpose: We evaluated the extent of changes in training practices, recovery, mental health, and sleep patterns of athletes during the early COVID-19 lockdown in a single country-cohort. Methods: A total of 686 athletes (59% male, 41% female; 9% World Class, 28% International, 29% National, 26% State, 8% Recreational) from 50 sports (45% individual, 55% team) in Malaysia completed an online, survey-based questionnaire study. The questions were related to training practices (including recovery and injury), mental health, and sleep patterns. Results: Relative to pre-lockdown, training intensity (-34%), frequency (-20%, except World-Class), and duration (-24 to 59%, especially International/World-Class) were compromised, by the mandated lockdown. During the lockdown, more space/access (69%) and equipment (69%) were available for cardiorespiratory training, than technical and strength; and these resources favoured World-Class athletes. Most athletes trained for general strength/health (88%) and muscular endurance (71%); and some used innovative/digital training tools (World-Class 48% vs lower-levels ≤34%). More World-Class, International, and National athletes performed strength training, plyometrics, and sport-specific technical skills with proper equipment, than State/Recreational athletes. More females (42%) sourced training materials from social media than males (29%). Some athletes (38%) performed injury prevention exercises; 18% had mild injuries (knees 29%, ankles 26%), and 18% received a medical diagnosis (International 31%). Lower-level athletes (e.g., State 44%) disclosed that they were mentally more vulnerable; and felt more anxious (36% vs higher-levels 14-21%). Sleep quality and quantity were “normal” (49% for both), “improved” (35% and 27%), and only 16% and 14% (respectively) stated “worsened” sleep. Conclusion: Lockdown compromised training-related practices, especially in lower-level athletes. Athletes are in need of assistance with training, and tools to cope with anxiety that should be tailored to individual country requirements during lockdown situations.